Life Course Outcomes for Juveniles: Contact with the Criminal Justice System as a Turning Point - Tauffner, Dominique (2018)
This research investigated the life course outcomes of respondents who have been arrested during adolescence. Although the creation of the juvenile justice system is relatively recent, only existing for 119 years, there is a need for data on the impact this system has on society. The pre-existing knowledge and literature on juvenile delinquency and the criminal justice system often fails to capture longitudinal data. Most scholars on this issue will discuss the immediate effects of things like incarceration and placement or what influences delinquency, ignoring the long-term consequences or life outcomes of those that have been arrested prior to 18. The purpose of this study is to better understand how juvenile arrests and delinquency may influence life outcomes throughout early adulthood. I utilized self-reported survey responses from the Toledo Adolescent Relationships Study (TARS) (N = 1,239) to gather longitudinal data for statistical analyses, which pre-exists the creation of this study. The data was critically evaluated with the support of univariate and bivariate modeling. Specifically, my bivariate statistical analyses included t-tests, chi-squared tests, and cross tabulations. Results show significant evidence to support the hypothesis that formal juvenile contact with the criminal justice system serves as a negative turning point in adolescents’ lives. This negative turning point results in poor life outcomes for the juveniles throughout early adulthood. Furthermore, those with greater frequency of arrests prior to 18 also report worse life outcomes when compared to those who have only been arrested once or never